Effects of eight weeks of Core Stability Exercises on Endurance and Strength of Core Muscles in Women with Rectal Prolapse - Marzieh Ramazani; Allahyar Arabmomeni; Khodayar Momeni (Complementary Medicine Journal of Faculty of Nursing and Midwifery)
Introduction: Pelvic organ prolapse is a condition, in which organs in the pelvis slip down and protrude into the vagina, causing many serious problems. Strengthening and stabilizing the core muscles is paramount for the prevention and treatment of this disease. Accordingly, the present study aimed to assess the effects of eight weeks of core stability exercise on endurance and strength of core muscles in women with rectal prolapse. Materials and Methods: In this quasi-experimental pre-test post-test study, 24 women with rectal prolapse in Isfahan with a mean age of 45.2 years and a body mass index of 26.2 kg/m2 were selected and participated with informed consent. The participants were randomly assigned to two groups (n= 12): core stability exercises and control. The exercise protocol was implemented incrementally for eight weeks, three sessions per week, each session lasting 30 min. Study variables were measured before and after the exercise program. In order to analyze the data, multivariate covariance test was used using SPSS software (version 26) at a significant level (P≤0.05). Results: The results of the study demonstrated a significant increase in the endurance of the flexor and extensor muscles of the central body region in the core stability exercises group (P≤0.05). Also, a significant increase in the strength of the trunk flexor and extensor muscles was observed in the Core stability exercises group (P≤0.05). Conclusion: These results show the effect of core stability exercises on increasing the endurance and strength of the muscles of the core body, which, as a result, may have positive effects on rectal prolapse. Therefore, it is suggested that sports therapy centers, doctors, and therapists use this exercise method to improve the condition of patients suffering from rectal prolapse.